CHANNEL CONSTITUENTS IN SYNTHETIC BERYL: AMMONIUM - Mashkovtsev R.I.; Solntsev V.P. (My University, 2002)
The infrared spectra and electron paramagnetic resonance (EPR) of channel constituents in beryls synthesized hydrothermally in the presence of NH4Cl were investigated. Two forms of ammonium ion were observed to be incorporated into the c -channel. IR-spectra show the double band at 3295 and 3232 cm−1 and two broad bands between 2600 and 3000 cm−1 which were assigned to the NH3 molecule and NH4+ ion, respectively. Similar N–H stretching vibrations are also observed in Regency hydrothermal synthetic beryls and can be used to separate these synthetic beryls from their natural counterparts. After γ-irradiation of hydrothermally grown samples at 77 K, the EPR of the NH3+(I) radical was observed. The NH3+(II) radical replaces the NH3+(I) radical when the sample is heated to room temperature. Both the NH3 molecule and the NH3+ radical have their C3 symmetry axes perpendicular to the crystal c-axis. The spin Hamiltonian parameters of the NH3+(I) are axial-symmetric due to the rapid rotation of the radical about the c-axis. The NH3+(II) radical has a low symmetry and shows a hindered rotation because of its shift from the c-axis position and an interaction with the proton in the near neighbourhood. Possible models for the paramagnetic centres are discussed.
Keywords: Beryl; Infrared spectroscopy; EPR; Ammonium